Invasive Cronobacter species infection in infants and children admitted to a rural Kenyan hospital with a high prevalence of malnutrition. (3rd July 2018) - Piper, Joe D.; Mwarumba, Salim; Ngari, Moses; Mvera, Benedict; Morpeth, Susan; Berkley, James A.
Abstract: For children with acute malnutrition, ready-to-use therapeutic foods (RUTF) are lifesaving treatments. In 2012, detailed testing detected Enterobacteriaceae including Cronobacter species at low levels in RUTF from all UNICEF-approved producers. Cronobacter in milk feeds has previously been associated with severe neonatal infections. Thus, given the susceptibility of severely malnourished children to invasive bacterial infections, concerns arose about the potential for Cronobacter infections from RUTF. This led to widespread production and supply problems in emergency feeding programmes. The KEMRI/Wellcome Trust Research Programme has conducted systematic surveillance for invasive bacterial infections among children admitted to Kilifi County Hospital, Kenya since 1998. 65, 426 paediatric blood and cerebrospinal fluid cultures from 52, 733 admissions resulted in 3953 with growth of a pathogenic organism. From the 60 Enterobacter and Cronobacter isolates, possible Cronobacter species were initially selected from their original API-20E biochemical profile, which was repeated and then confirmed using ID-32E. Only two isolates were consistent with Cronobacter species, neither case had received RUTF. Serious infection due to Cronobacter species does not have a significant burden in this population. This has important implications for the continued supply, manufacture and monitoring of emergency feeds for malnourished children.